1986
DOI: 10.1021/ac00126a041
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution spatially resolved visible absorption spectrometry of the electrochemical diffusion layer

Abstract: M through 1 X lo4 M. The slope of the calibration curve was 0.506 f 0.035 pA/pM. The minimum detectable difference between the background and sample solution estimated by paired measurements (5) was 0.025 pM, which is over an order of magnitude lower than in the dc polarographic method (1 7).A voltammogram of a 5.0 X lo4 M Ti(IV) solution is presented in Figure 10. ACKNOWLEDGMENTThe authors thank Janet Osteryoung for helpful discussion.(1) Brdicka, R.; Wlesner, K.Concentration vs. distance profiles are fundame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 44 publications
1
39
0
Order By: Relevance
“…The apparatus is similar to those described by Fukanaka et al (19) and later by McCreery and co-workers (20,21) for imaging the electrochemical diffusion layer at a solid electrode. Those authors have reported the spatial resolution due to diffraction from the lenses and refractive index effects is limited to 2 pm (19, 21), and due to edge diffraction effects a resolution of less than 5 pm is estimated near the electrode edge (21). We have recently reported the details of the design of the instrument and the electrochemical cells used to probe the distribution and diffusion rate of HzO inside a PVC-based membrane, using water-sensitive (solvatochromic) dyes (22).…”
Section: Introductionmentioning
confidence: 99%
“…The apparatus is similar to those described by Fukanaka et al (19) and later by McCreery and co-workers (20,21) for imaging the electrochemical diffusion layer at a solid electrode. Those authors have reported the spatial resolution due to diffraction from the lenses and refractive index effects is limited to 2 pm (19, 21), and due to edge diffraction effects a resolution of less than 5 pm is estimated near the electrode edge (21). We have recently reported the details of the design of the instrument and the electrochemical cells used to probe the distribution and diffusion rate of HzO inside a PVC-based membrane, using water-sensitive (solvatochromic) dyes (22).…”
Section: Introductionmentioning
confidence: 99%
“…Using electrode potential modulation, it was possible to detect species down to 2 × 10 −8 M [173]. The technique was shown to work with a continuum source [174].…”
Section: Glancing Incidence Reflection Near-parallel or Parallel Refmentioning
confidence: 99%
“…Herein, we demonstrate a new means to visualize electrochemical reactions by the fluorescence quenching of the ZnS-AgInS 2 solid solution (ZAIS) NPs caused by electron transfer as a probe. In situ techniques to observe an electrochemical diffusion layer had been reported using a specially modified microscopy with diode array detector, [18][19][20] a confocal Raman microscopy, [21][22][23][24] and recently by a scanning electron microscopy with an x-ray spectrometer. 25 The present method detecting the variation in polarity can, in principle, cover many types of redox reactions if semiconductor NPs with an appropriate energy level and polarity are selected.…”
Section: Introductionmentioning
confidence: 99%